Does Work-Family Conflict Affect the Auditor’s Performance?: Examining the Mediating Roles of Emotional Exhaustion and Job Satisfaction - Yustina, Andi Ina; Valerina, Tifanny (Gadjah Mada International Journal of Business, 2018)
This paper examines whether the work-family conflict (related to both work-interfering-family and family-interfering-work) of auditors affects their performance and if so, whether the effect is mediated by emotional exhaustion and job satisfaction. A mail survey is used to deliver a questionnaire to 151 auditors from ten CPA firm in Indonesia. The result shows that emotional exhaustion and job satisfaction fully mediates the relationship of work-family conflict with job performance. The result also demonstrates that Work-Interfering-Family (WIF) has significant effects on emotional exhaustion and job satisfaction, but Family-Interfering-Work (FIW) has no significant influence on either emotional exhaustion or job satisfaction. This study suggests that maintaining a regular training program for auditors, having flexible working arrangements, and encouraging a healthy lifestyle may help to reduce the work-family conflict and will increase the job satisfaction and performance of auditors.